Penggunaan Modul Projek Penguatan Profil Pelajar Pancasila Bermuatan Kearifan Lokal di SD Negeri 4 Tiga - Widnyani, Ni Wayan Apri; I Wayan Numertayasa; Ni Putu Eni Astuti (Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze the effectiveness and implementation of the Pancasila Student Profile Strengthening Project (P5) module, containing local wisdom, in improving the understanding and character of elementary school students. The phenomenon of globalization often erodes local cultural values ​​among the younger generation. The P5 module, with its local wisdom, is expected to be a bridge to introduce, preserve, and instill noble local cultural values ​​in students from an early age. The research method used is a case study with a qualitative approach, involving observation, interviews, and document analysis in several elementary schools that have implemented this module. The results show that the use of the P5 module containing local wisdom significantly increases students' awareness of their cultural identity, strengthens the character of the Pancasila student profile, such as mutual cooperation and global diversity, and increases learning motivation through direct experience. The implementation of this module faces challenges in terms of developing relevant content and adequate teacher training, but it makes a positive contribution in shaping a young generation that is proud of its culture and has a strong character. The implications of this study are the importance of developing an adaptive and contextual curriculum, as well as continuous training for teachers to maximize the potential of local wisdom as a valuable learning resource